Analisis Penggunaan Alih Kode Pada Percakapan Informal Mahasiswa di Kelas (An Analysis of Code-Switching in Informal Conversations Among College Students in the Classroom) - Ananda Devi Permata Sari; Berlian Nabiila Wijayanti; Vivian Natasya Putri; Wiwik Yulianti; Yvonne Rennesia Gulo (Translation and Linguistics (Transling), 2026)
This study analyzes code-switching in some cases of informal classroom conversations among students from diverse regional backgrounds. The linguistic diversity within the campus environment makes code-switching a natural phenomenon that frequently occurs in daily interactions, especially before lectures begin. This research employs a descriptive qualitative method using observation and spontaneous conversation recording techniques involving two or more students. Data analysis is conducted using Fishman’s theory, which emphasizes the relationships among language choice, domain, and underlying social functions. The findings indicate that code-switching appears in both internal and external forms, occurring inter-sententially and intra-sententially. In the seven cases examined, code-switching is used to build rapport, reinforce group identity, clarify meaning, and adjust to the situation and interlocutors. Factors influencing the occurrence of code-switching include linguistic diversity within the class, conversational context, language habits, and specific communicative purposes. This study concludes that code-switching is a natural and adaptive communication strategy that plays an important role in maintaining smooth social interactions in a multilingual classroom environment. his research also contributes academically to enriching sociolinguistic studies on language use among students.Penelitian ini bertujuan untuk menganalisis penggunaan alih kode dalam tujuh kasus percakapan informal mahasiswa di kelas yang terdiri dari penutur dengan latar belakang daerah yang beragam. Keberagaman linguistik di lingkungan kampus membuat alih kode menjadi fenomena yang wajar dan sering muncul dalam interaksi sehari-hari, terutama sebelum perkuliahan dimulai. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik observasi dan pencatatan percakapan spontan antara dua orang atau lebih mahasiswa. Analisis data dilakukan dengan menggunakan teori Fishman yang menekankan hubungan antara pilihan bahasa, domain, dan fungsi sosial yang melatarbelakanginya. Hasil penelitian menunjukkan bahwa alih kode muncul dalam bentuk internal maupun eksternal, baik secara inter-sentensial maupun intra-sentensial. Pada tujuh kasus yang dikaji, alih kode digunakan untuk membangun kedekatan, menegaskan identitas kelompok, memperjelas maksud, serta menyesuaikan diri dengan situasi dan lawan bicara. Faktor pendorong terjadinya alih kode meliputi keberagaman bahasa daerah dalam kelas, konteks percakapan, kebiasaan berbahasa, serta tujuan komunikatif tertentu. Penelitian ini menyimpulkan bahwa alih kode merupakan strategi komunikasi yang alami, adaptif, dan berperan penting dalam menjaga kelancaran interaksi sosial di lingkungan kelas yang multilingual.